Postępowanie w sprawach o przestępstwa popełnione przez pracowników kolei w latach 1944-1949 w świetle akt zachowanych w zasobie Archiwum Państwowego w Gorzowie Wielkopolskim - przyczynek do badań nad orzecznictwem Wojskowego Sądu Polskich Kolei Państwowych = Proceedings in offenses committed by railroad employees in years 1944-1949 in the light of the records kept in the resources of the State Archives in Gorzow Wielkopolski - Contribution to the case studies of the Militar y Courts of the Polish State Railways - Siemaszko, Karol (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Military Court of Polish National Railways was a subject of research but until now nobody conducted research of judicature of this court and its departments in Poznan and Wrocław. The author discuss in this article two cases which had survived in State Archive in Gorzow Wielkopolski. This article is only contribution and is starting point of deeply researches on judicacture of Military Court of Polish National Railways.
Keywords: Wojskowy Sąd PKP; komunistyczne prawo karne; kodeks wojskowego postępowania karnego; Military Court of Polish National Railways; communist penal law; military code of penalprocedure